Strategi Komunikasi Pemasaran Dalam Meningkatkan Hasil Penjualan Produk Studi Kasus PT. Nazar Paint Cabang Cat Kiloan Sibolga - Hutagalung, Annisa Sapriannur; Syahminan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2024)
The purpose of this study is to identify and analyze the problems that arise as a result of the ineffectiveness of marketing communication strategies used with SWOT analysis techniques and the 4 P Mix Marketing theory, as well as to assist in finding solutions to what causes product sales results to be lower than those in Java. So the data processing method employed in this study is a qualitative descriptive method, with data collection procedures including in-depth interviews, field observations including informants as a source of information about marketing Nazar Paint kilo wall paint, and recording. The results of this study indicate that the Marketing Strategy that has been designed in such a way is less able to increase product sales results because the marketing strategy used has not been implemented systematically. Furthermore, the utilization of communication media is also not optimally carried out by Nazar Paint Distributor Agents. Sibolga Branch has not fully utilized social media and other digital media that can reach a wider and more diverse audience, so there is a need for Marketing Strategies that must be added to the list of Nazar Paint Sibolga marketing strategy planning is using new media in the form of social media and related to the lack of creativity in the marketing strategy applied, In this case, the agent must be able to create innovations that will be the key to attracting consumers. For example, by utilizing unique or distinct advertising features that can distinguish Nazar Paint from its competitors, such as the employment of wind dolls in front of the business as one of the attractions for consumers to visit Nazar Paint Kiloan Sibolga Paint Branch